Shell dissolution rates differ fourfold between mussel species - Rachel R. Carlson; Mazie A. Lewis; Aaron T. Ninokawa; Alisha M. Saley; Tessa M. Hill; Brian Gaylord (Royal Society Open Science)
Ocean acidification poses a critical threat to marine calcifiers globally and is particularly severe in the California Current System, where ecologically and economically important bivalves experience reduced calcification under climate change. Marine mussels display differential habitat preferences, with species like Mytilus californianus favouring fully saline environments and M. trossulus inhabiting sites with greater freshwater input. Determining abiotic dissolution rates of these species under ocean acidification is essential for predicting future consequences of climate change for coastal populations. We examined shell dissolution rates of mussel congeners under a range of pH (6.5–9.3) and aragonite saturation states (0.1–9.0). We also experimentally quantified the relative importance of dissolution from interior versus exterior shell surfaces. M. trossulus exhibited fourfold higher shell dissolution rates than M. californianus. When the shell interior was sealed against seawater exposure, dissolution rates decreased significantly in both species, indicating high abiotic dissolution on the shell interior. Results demonstrate that dissolution rates can vary between congeners inhabiting the same biogeographic region. Our finding that freshwater-tolerant M. trossulus has higher abiotic dissolution under ocean acidification is important because low salinity may further retard calcification, altering future intertidal population structure along freshwater-influenced coastlines.